2019
DOI: 10.1186/s12966-019-0838-x
|View full text |Cite
|
Sign up to set email alerts
|

Culture and community: observation of mealtime enactment in early childhood education and care settings

Abstract: Background Establishing healthy eating behaviours in early life has implications for health over the life course. As the majority of Australian children aged five and under regularly attend early childhood education and care (ECEC) services, mealtimes at ECEC settings present opportunities to promote healthy eating behaviors. The purpose of this study was to explore children’s eating behaviours and interactions between peers and educators during mealtimes in ECEC settings, with the aim of construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
0
11
0
4
Order By: Relevance
“…Participants remarked that this appeared to limit involvement of children in mealtime preparations, and was not conducive to role-or peer-modelling, nutrition education or child self-regulation. Harte et al (2019) [65] described mealtimes at childcare as a "unique cultural phenomenon", with important routines and rituals that can be used by childcare educators to support the development of healthy eating behaviours and food preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Participants remarked that this appeared to limit involvement of children in mealtime preparations, and was not conducive to role-or peer-modelling, nutrition education or child self-regulation. Harte et al (2019) [65] described mealtimes at childcare as a "unique cultural phenomenon", with important routines and rituals that can be used by childcare educators to support the development of healthy eating behaviours and food preferences.…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, a Harvard cohort study found that children who eat together with their parents are twice as likely to eat their five servings of FV compared to families who do not share their meals. Moreover, in the same study, family meals seemed to help parents to perform as role models and be considered as an example of polite table manners and healthy eating habits [ 58 ]. In addition, results from the same study also showed that shared meals seem to help in childhood obesity prevention as children tend to eat less when they eat in the presence of their parents [ 58 ].…”
Section: Parental Dietary Behaviors Influence On Children’s Eating Habitsmentioning
confidence: 99%
“…Moreover, in the same study, family meals seemed to help parents to perform as role models and be considered as an example of polite table manners and healthy eating habits [ 58 ]. In addition, results from the same study also showed that shared meals seem to help in childhood obesity prevention as children tend to eat less when they eat in the presence of their parents [ 58 ]. Participants in this study were children of nurses, hence, they all came from highly educated families compared to the general population [ 58 ].…”
Section: Parental Dietary Behaviors Influence On Children’s Eating Habitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selv om mange studier viser til at dersom voksnes perspektiv dominerer og styrer barns handlinger og aktiviteter, og at det kan vaere til hinder for barnas muligheter for å medvirke, finnes det også nyere forskning som nyanserer dette bildet (Greve, 2009;Harte et al, 2019;Koivula & Hännikäinen 2017;Tofteland, 2015). Det illustreres for eksempel hvordan personalets ivaretakelse av vennskaps-og fellesskapsrelasjoner skaper muligheter for barns medvirkning (Greve, 2009).…”
Section: Medvirkning Og Voksnes Perspektiv Versus Barns Perspektivunclassified